Customary Law in Timor-Leste - Santos, Hercus Pereira dos (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Democratic Republic of Timor-Leste as a modern state is governed by its Constitution, which was drawn up by the Constituent Assembly in 2001 with the presence and fundamental support of the United Nations Transitional Administration in Timor-Leste – UNTAET (United Nations Transitional Administration in East Timor), under the leadership of the late Sergio Viera de Melo. This means that Timor-Leste, as a logical consequence, was founded on the foundations of the Western Roman-Germanic legal doctrine and especially of Portugal. We can clearly see that the Constitution of Timor-Leste integrates the basic and important foundations of the modern rule of law where the supremacy of positive state rights prevails: The Constitution and other state legal norms, respect for human rights, democratic culture, the principle of separation of powers, political, social, religious pluralism and the determination to fight any tyranny, dictatorship and at the same time the Constitution of Timor-Leste also seeks to resepitate cultural pluralism, the customary right existing within the society of Timor-Leste to create a just and prosperous state for all citizens. That is why we can safely say that the Constitution of Timor-Leste as a fundamental law of the state seeks to guarantee that Timor-Leste, on the one hand, as a modern state of law based on Western legal standards and on the other hand, the Constitution itself seeks to value and respect the use of customary law that is still in use to regularize the life of the people within the society of Timor-Leste.